Perinatal, maternal and antenatal associated factors for autism: a case control study - Abdullah, Mohammad Nasir (Universiti Sains Malaysia, 2011)
Autism disorders are a group of neurodevelopmental disorders which characterized into three main domains which are social interaction impairment, communication delay and repetitive or stereotypic behavior. Many studies had suggested that the risk factors for autism derive from three big factors namely environmental factors, genetic predisposition and vaccine induced. The aim of this study was to investigate the perinatal, maternal and antenatal associated factors on autistic disorder children at Hospital Pulau Pinang and Hospital Bukit Mertajam, Pulau Pinang. A case control study involving 312 cases and control was conducted using data retrieved from hospital records at Pulau Pinang hospital and Bukit Mertajam hospital from 2001 to 2008. The departments involved were Psychiatric, Obstetrics and Gynecology and Record and Management Department. All cases which met the inclusion and exclusion criteria were included in the study. Univariable and multivariable logistic regression were used to explore the prenatal/perinatal risk factors associated with autistic disorder children. There were seven risk factors contributed most to autistic disorder determination. The factors were maternal age [Adjusted OR: 1.41; 95% CI: (1.27, 1.57)], maternal smoking reported at first antenatal visit [Adjusted OR: 13.61; 95% CI: (1.87, 99.35)], birth asphyxia [Adjusted OR: 0.35; 95% CI: (0.11, 1.08)], psychiatric history [Adjusted OR: 54.94; 95% CI: (12.07, 250.04)], multiple gestation [Adjusted OR: 4.81; 95% CI: (1.86, 12.45)], parity for more than 4 [Adjusted OR: 0.11; 95% CI: (0.03, 0.47)], parity between 0 and 1 [Adjusted OR: 0.19; 95% CI: (0.07,0.55)], Chinese race compared to the Malay race [Adjusted OR: 10.11; 95% CI: (3.61, 28.30)] and Indian race compared to the Malay race [Adjusted OR: 5.14; 95% CI: (1.38, 19.16)]. The results suggested that autistic disorders were associated with perinatal, maternal and antenatal factors such as delivery, pregnancy and maternal characteristics.